Understanding Theoretical Frameworks in Gender Studies: Feminism, Postfeminism, and Islamic Feminism - Andhina Qaddis Fithratana; Bunga Aminah Salsabila; Rosida, Ida (UIN Syarif Hidayatullah Jakarta, 2025)
This paper discusses feminist movements from the first wave, second wave, third wave, and post-feminism and highlights Islamic feminism. Feminism occurred in the 19th and early 20th centuries and focused on fighting for women’s rights. These feminism concepts are highly important to see the ongoing phenomenon within society engaging with gender issues such as gender inequality, discrimination, and violence against women. This research provides a deeper understanding of the growth of the feminist movement and related issues in social, cultural, and political contexts as well as current issues that are connected to it. This highlights the theoretical developments and its critical debates. This paper was written using a systematic literature review method to find out how the feminist movement develop from the past to the present time. The aim of a literature review is to acquire a theoretical foundation that can help resolve the study challenge and strengthen the researcher's analyisis on gender issues. Discrimination against women was pervasive and affected women’s life particularlt for gender constraints. Still, women's place in society was seen as inferior and unequal. Through developing feminism, women are able to stand up for their rights, achieve their goals of gender equality and justice.